Changes in habitat suitability for waterbirds of the Momoge Nature Reserve of China during 1990–2014 - Zhang, Yue; Wang, Zongming; Ren, Chunying; Yu, Hao; Dong, Zhangyu; Lu, Chunyan; Mao, Dehua (Journal of Environmental Engineering and Landscape Management, 2017)
There is increasing empirical evidence that changes in habitat quality play an important role in determining species distributions and biodiversity. However, most research has focused on habitat quality, and we still lack approaches for tracking habitat quality dynamics. In this paper, by establishing qualitative and quantitative relationships between waterbird populations and key habitat indicators such as water abundance, food, shelter conditions and disturbance, we developed an object-oriented classification method, in conjunction with a geographic information systems (GIS) based centroid moving method, to assess habitat suitability dynamics for waterbirds at the Momoge Nature Reserve, China. Our results showed that habitat suitability improved during 1990–2000 and declined during 2000– 2014. Habitats with very good and good grades increased by 71.47 km2 (4.88%) during 1990–2000 and decreased by 200.66 km2 (13.78%) during 2000–2014. The habitat area with a good grade moved to the north, while the habitat area with a poor grade moved to the south during 1990–2014. This was mainly because the surrounding cropland area increased and shifted as oil and gas projects developed. These findings suggest that our object-oriented classification and centroid moving methods have great potential for use in biodiversity conservation and ecosystem management.